2020
DOI: 10.1016/j.gexplo.2020.106557
|View full text |Cite
|
Sign up to set email alerts
|

A regional soil and river sediment geochemical study in Baoshan area, Yunnan province, southwest China

Abstract: status of surface environments in the Baoshan area have been revealed * Chemical elements in study area are mainly controlled by geology and geomorphology * Land use types also show its contributions to pH in soil * Agricultural fertilization caused enrichment of the nutrient elements in surface soil * Mining activities are the main reason for PTMs enrichment in surface soil near mine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 79 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…The Baoshan area is located in Yunnan province, Southwest China (Figure 1a), has a low latitude and moderate elevation, and is tempered by a mild subtropical climate with short, mild, and dry winters and warm, wet summers. Variations in the average temperature are closely connected to altitude, while the western and southern parts of the study area experience the highest amount of rainfall [54,55,64]. The main land-use types in the study area are forested land, dry cultivated land, paddy land, grassland, and garden plots, with few water areas or other land types (residential quarters, industrial and mining land, and unused land) (Figure 1c) [54,55].…”
Section: Study Areamentioning
confidence: 93%
See 4 more Smart Citations
“…The Baoshan area is located in Yunnan province, Southwest China (Figure 1a), has a low latitude and moderate elevation, and is tempered by a mild subtropical climate with short, mild, and dry winters and warm, wet summers. Variations in the average temperature are closely connected to altitude, while the western and southern parts of the study area experience the highest amount of rainfall [54,55,64]. The main land-use types in the study area are forested land, dry cultivated land, paddy land, grassland, and garden plots, with few water areas or other land types (residential quarters, industrial and mining land, and unused land) (Figure 1c) [54,55].…”
Section: Study Areamentioning
confidence: 93%
“…This phenomenon can be observed in the soils of the Baoshan area in Yunnan province, southwest China, where mineral resources and carbonate and basalt parent materials are widely distributed [54,55,64]. Previous study has shown the concentrations and the distribution of selected elements (including PTEs) in the soil and river sediments of the Baoshan area, based on the data from the 1: 250,000 scale National Geochemistry Survey of Land Quality project (NGSLQ) and archived river sediment samples collected and analyzed in the Regional Geochemistry-National Reconnaissance (RGNR) program based in this area (6220 km 2 ) [54]. The distribution of PTEs in surface and deep soil are mainly influenced by natural factors (basic igneous rocks, carbonate rocks, and mineralization), while the surface soil near mining areas is aggravated by mining related activities in the Baoshan area [54,55].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations